Effect of dehydrogenation holding time after black oxide coating on AISI 4340 steel on mechanical properties: Pengaruh waktu penahanan dehidrogenasi setelah pelapisan black oxide pada baja AISI 4340 terhadap sifat mekanik - Adinda Fadhila; Devi Eka Septiyani Arifin (Fakultas Teknik, Universitas Lampung, 2026)
In the automotive industry, especially in labor-intensive industries such as PT XYZ which produces all components independently, the black oxide coating process is often applied to improve corrosion resistance, especially on AISI 4340 steel. However, this process has the potential to cause hydrogen embrittlement phenomena due to immersion in chemical solutions. One method to overcome this problem is the dehydrogenation (baking) process, which is thermal heating to remove hydrogen and restore the mechanical properties of the material. This study aims to analyze the effect of black oxide coating without dehydrogenation process and variation of dehydrogenation holding time on mechanical properties of AISI 4340 steel, including tensile strength, hardness, and oxalic acid drop test. The dehydrogenation process variation consists of specimens without dehydrogenation, as well as specimens with dehydrogenation process for 3 hours and 4 hours at 190±14°C. The test results show that the increase in dehydrogenation holding time is directly proportional to the increase in tensile strength and hardness of the material. The percentage increase in tensile strength between the 3-hour and 4-hour specimens reached 2.64%, while the increase in hardness was 3.96%. Specimens without dehydrogenation process showed lower tensile strength and hardness values.